Assessing tax relief from targeted investment tax incentives through corporate effective tax rates Methodology and initial findings for seven Sub-Saharan African countries - Celani, Alessandra (OECD Publishing, 2022)
Corporate tax incentives reduce investment costs for businesses, which may affect investment and location decisions. They apply through different designs and interact with countries' standard tax systems, often making it difficult for tax policy makers and researchers to compare their generosity and assess their impacts across countries. This paper develops a methodology to calculate forward-looking corporate effective tax rates (ETRs) summarising tax relief from investment tax incentives into comparable indicators. It presents ETR indicators for seven Sub-Saharan African countries. Empirical results show that tax incentives substantially lower corporate taxation across these countries. On average, tax incentives reduce ETRs by 30% in the food and automotive industries compared to the standard tax treatment. ETRs often differ among taxpayers in a same sector and country - by up to 55%. The most generous tax treatment is typically offered within Special Economic Zones, where tax incentives can reduce ETRs to near zero
Keywords: Taxation; Development; Industry and Services; Finance and Investment; Angola; Botswana; Eswatini; Kenya; Mauritius; Senegal; South Africa